Detection and Monitoring of Temporal Changes and Distribution of Cultivable Lands in Shahr-e-Kord Plain; Using Landsat and Sentinel-2 Data - Sh. Mahdian; A. Amini; M. Bagheri Bodaghabadi; Z. Mosleh (Desert, 2023)
The use of accurate and upto date information is crucial for sustainable resourcemanagement in agriculture. Satellite imagery provides the opportunity for thecomprehensive monitoring of resources, and enables precise planning not onlyfor rural developm ent and agricultural sectors but also for national developmentprograms and the implementation of food and water security policies in thecountry. It also helps prevent land use changes and their degradation. In thisresearch, an attempt has been made to c alculate the cultivable land area in Shahre Kord Plain located in Chaharmahal va Bakhtiari Province. The imagery data ofLandsats 7 8 and Sentinel 2 satellites were obtained in the form of NDVI indexduring the period from 2013 to 2022 , which processed an d validly classified usingunsupervised algorithms in GIS environment. All existing features wasdifferentiated based on digital number values and green area surfaces identifiedfor different time periods. The sound and secure areas of cultivation werecon sidered based on the frequencies of plantation during the 2013 2022 . Averageof the agricultural lands approximated 9,392 ha. Due to recurrent water shortagesin recent years, only about 2,603 ha of agricultural lands in the study region havebeen under pe rmanent cultivation over the 8 year study period and the rest havebeen abandoned over time or left for fallow and livestock grazing. Accordingly,as a basis for the integrated land water crop system planning and recommendingpolicy for conservation of per manently cultivable land resources in theagricultural system of the region, the map of their spatiotemporal distribution wasprepared and presented with a pixel specific precision, by different years ofcultivation.